Biogas-fuelled aqua-ammonia absorption refrigeration as a means of reducing post-harvest losses in rural Sub-Saharan Africa - Wentzel, Louis Frans Jacobus (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.